One example of the artistic feature of the rhyme of the long song “Tsoor” - Soyolt, Munkhbayar (Studia Folclorica, 2024)
In this article, the author has selected the song ‘Altan Arura’ from the Mongolian long song “tsoor” duun and analysed it from the point of view of folk song poetry and literary poetics. The author concluded that there is little research on the poetry of the long song ‘Tsoor’ and set his main goal to reveal the artistic features of the song. To achieve this aim, apart from the vocabulary of this song, in a certain order of analysis such as, theme, genre and poetic structure of the poem and special attention is paid over the rhyme and epistrophe lyrics of this long song. The author has made a comparative analysis over several versions of the song as well as the couplets of such long songs as ‘Avral gurvan chukhag bogd’ and ‘Tsogtsolson buyani urs’. The author concluded that this song was sung on any state or religious holiday, praising and wishing for peace and equality, describing the beauty of the holiday time. Цоор уртын дууны уран холболтын нэгэн жишээ Хураангуй: Өгүүлэлд цоорын уртын дуунаас “Алтан арура181 хэмээх дууг сонгон авч аман зохиол болон уран зохиолын шүлэг зүйн үүднээс задлан шинжилгээ хийжээ. Зохиогч цоорын дууны шүлгийг судалсан зүйл цөөн байгаад үндэслэн энэхүү сэдвийг сонгон авч тус дууны уран сайхны онцлогийг нээн илрүүлэхийг гол зорилгоо болгосон байна. Зорилгоо биелүүлэхийн тулд энэ дууны шүлэгт үгсийн сангаас гадна сэдэв, төрөл зүйл, шүлгийн зохиомжийг тодорхой дэс дарааллаар задлан үзэхдээ шүлгийн сүүл холбоц (rime), уран найруулгын давталт (epistrophe)-ыг гол болгон тайлбарлажээ. Тус дууны хэд хэдэн хувилбар “Аврал дээд гурван богд”, “Цогцолсон буян үр” зэрэг дууны шүлэгтэй зэрэгцүүлэн үзэж найрын дууны дотор төр, шашны ямарваа найрт дуулдаг, эв эе, амар жаргалан буюу найралдах үеийн сайхныг өгүүлсэн энх амгалан, эрх тэгш чанарыг магтан хүсэмжилсэн агуулгатай хүндэтгэлийн дуу гэж үзжээ. Түлхүүр үг: цоор дуу, уртын дуу, дууны шүлэг, толгой холболт, сүүл холбоц, үг давталт, уртын дууны уран сайхан